Clinical Assessment of Several Risk Variables Linked to Surgical Site Infections in a Tertiary Hospital - Agrawal, SurajKumar K.; Pradhan, Tanu Deepak Kumar; Rewale, Venktesh (Journal of Biomedical and Pharmaceutical Research, 2021)
Background: Surgical site infections (SSI) are the most common nosocomial infection for surgical patients. They have been found to be the primary cause of operation-related adverse events and commonly cause morbidity and mortality among hospital inpatients. Aims & objectives: The goal of the current study was to investigate different risk variables for surgical site infections at a tertiary hospital. Material and Methods: The current investigation was a prospective, observational, hospital-based study that included patients of any gender, ages 18 to 70, who had non-traumatic exploratory laparotomies and surgical site infections afterward. Results: During the study period, 162 patients had surgical site infections (1664 laparotomies), meaning that the incidence of SSI was 6%. The majority of cases (64 %) and age group (28 %) were male. Diabetes (43%) was the most common co-morbidity observed, followed by hypertension (25%) BMI 25–30 kg/m2, dyslipidemia (33%) smoking (28%) and dyslipidemia (45%). 51% of patients had an ASA score of 2, and 53% had surgeries lasting more than two hours. Exploratory laparotomy with appendicectomy and peritoneal lavage had the highest rate of SSI (28%), with open appendicectomy (15%), adhesiolysis/resection anastomosis (11%), and peritoneal lavage coming in second and third, respectively. The majority of wounds (46%) were clean, with clean contaminated wounds (30%), contaminated wounds (16%), and dirty or infected wounds (9%). In the current investigation, the most prevalent SSI was superficial (65%), followed by deep (28%) and organ space (6%). E. Coli was the most frequently isolated organism (20%), followed by Pseudomonas (16%) and Streptococcus (14%). In 66 cases (41%), there was no discernible growth. Conclusion: Infections at the surgical site are avoidable complications. High-risk factors for surgical site infections were BMI > 25, co-morbidities like diabetes, smoking, dyslipidemia, surgery lasting more than two hours, and appendectomy. Keywords: Surgical site infection, diabetes, smoking, dyslipidaemia, abdominal surgeries.